"Violent propensity, strain, and violent intentions: a test of Agnew's revised conditioning hypothesis". Issue 1 (2nd January 2019) - Willits, Dale
ABSTRACT: General Strain Theory's (GST) mediating and conditioning hypotheses suggest that emotions mediate the strain-crime relationship and that personality traits condition the effects of strain. Individual-level research provides weak-to-mixed support for these hypotheses, leading to calls to revise GST. Yet, the mediating and conditioning hypotheses provide situational predictions which are largely untested at the situational-level. Further, Agnew (2013) recently suggested a modified method of testing the conditioning hypothesis. This research, using factorial survey data from 734 college students, presents a situational test of this revised version of GST. Results are generally, but not fully, supportive of the mediating and conditioning hypotheses. This indicates that Agnew's most recent theoretical revision may be better suited for capturing the conditioning effect and that it is important to conduct more situational research on GST.